Nannochloropsis gaditana grown outdoors in annular photobioreactors: operation strategies - Nogueira, Natacha (2021)
Microalgae are a topic of intense research due to their potential applications in bio-based economy. However, sustainable commercial production is still overpriced due to high cultivation costs, harvesting and dewatering processes. In the present study, trials were conducted with the aim to improve daily operation strategies related to microalgae harvesting processes that did not compromise biomass productivity or the biochemical composition of the cultivated microalgae. Two experimental trials were performed in outdoor tubular annular photobioreactors to evaluate the effects of harvesting and medium dilution time (sunrise vs sunset) on Nannochloropsis gaditana biomass productivity, lipid and fatty acid content. Results showed that harvesting time had no significant effect on cell concentration and biomass productivity. Harvesting and medium dilution time did not affect lipid content. However, lipid content in samples collected at sunset was significantly higher than in samples collected at sunrise for both experimental treatments. The fatty acids profiles were mainly composed by polyunsaturated fatty acids, followed by mono-unsaturated fatty acids and saturated fatty acids. Regardless of medium dilution time, harvesting at sunset indicated that lipidic production (higher polyunsaturated fatty acids and lower saturated fatty acids) was favored without affecting the biomass productivity. The current study showed harvesting in the afternoon is a viable option for large production units that use semi-continuous strategy, without compromising biomass cell and lipid productivity.